WORKING HOURS AND MANDATORY BREAKS FOR MOBILE WORKERS AND DRIVERS IN ROAD TRANSPORT ACCORDING TO THE AMENDMENTS TO REGULATION (EC) 561/2006 - Matija Gočin; Sandra Debeljak; Miljenko Gočin (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In this paper, the authors deal with the amendments to Regulation (EC) 561/2006, which refer to working hours and mandatory breaks for mobile workers and drivers. The reasons for the amendment of the Regulation are presented and the positions of the EU member states on this matter are explained. Amendments to Regulation (EC) 561/2006, which the authors deal with in the paper, include amendments related to the permitted driving time for drivers, possible deviations from that time, weekly breaks and places where they can be taken, as well as their possible interruptions and records. The paper also researched and analyzed the results of a survey among professional drivers to whom this Regulation applies.